Consumer motivation and willingness to pay for "safer" vegetables in Ghana. Issue 3 (2nd March 2015) - Yahaya, Iddrisu; Yamoah, Fred A.; Adams, Faizal
Abstract : Purpose: – The purpose of this paper is to assess consumer motivation and willingness to pay (WTP) for "safer" vegetables from the use of non-treatment options of wastewater use in urban/peri-urban vegetable production. Design/methodology/approach: – As a theoretical basis, consumer theory of maximizing utility being an indicator of individual preference was examined through choice experiment (CE) method to measure the WTP for value of safety within the context of health reduced risk (pathogen reduction) of illness. WTP was tested empirically using survey data from 650 households in the two largest cities in Ghana (Accra and Kumasi) that are characterized by a number of well-established vegetable producers who use wastewater in their production and a large urban and peri-urban vegetable consumer market. Findings: – Experience of vegetable borne diseases drives the need for safer vegetables and income and gender are key demographic factors influencing WTP. It was further found that consumers are willing to pay an average amount of GH¢ 4.7 ($2.40) per month for a technology change that would result in the production of "safer" vegetables. Research limitations/implications: – Understanding WTP offers insight into consumer concerns, behaviour and their readiness to pay for safer vegetable options. However, a further consideration of the impact of the combinations of the various non-treatment options on pathogen reduction and the assessment of the financial viability of each option will collectively ensure an efficient and cost-effective implementation of the technologies. Practical implications: – WTP insight gained has implications for vegetable production, marketing and public health policy. The understanding from the findings forms a solid basis to canvass for certification system for urban/peri urban vegetables. The information provided also helps to formulate effective public education on the safety of vegetables. Originality/value: – Measuring WTP for safer vegetables by Ghanaian urban/peri-urban consumers is novel. The CE approach is robust and the findings can inform vegetable production and marketing decisions as well as public health policy formulation.